The extraction of microplastics from sediments: An overview of existing methods and the proposal of a new and green alternative. (September 2021) - Bellasi, A.; Binda, G.; Pozzi, A.; Boldrocchi, G.; Bettinetti, R.
Abstract: Microplastics (MPs) contamination is an existing and concerning environmental issue. Plastic particles have been observed worldwide in every natural matrix, with water environments being the final sink of dispersed MPs. Microplastic distribution in water ecosystems varies as a function of multiple factors, including polymer properties (e.g., density and wettability) and environmental conditions (e.g., water currents and temperature). Because of the tendency of MPs to settle, sediment is known to be one of the most impacted environmental matrices. Despite the increasing awareness of their diffusion in sediments, a proper quantification of dispersed particles is still difficult, due to the lack of standard protocols, which avoid a proper comparison of different sites. This hampers the current knowledge on environmental implications and toxicological effects of MPs in sediments. In this work, we examined 49 studies carried out from 2004 to 2020 to describe the different extraction methods applied, and to highlight pros and cons, with the aim of evaluating the more promising protocols. Therefore, we evaluated each proposed method by considering precision, reproducibility, economic viability and greenness (in term of used reagents). Finally, we proposed a valid alternative procedure in term of reliability and costs, which can attract increasing interest for future studies. Graphical abstract: Image 1 Highlights: Microplastics (MPs) contamination is an environmental issue. Plastic particles have been observed almost worldwide in every natural environments. A proper quantification of dispersed particles in sediments is still difficult. Different extraction methods of MPs from sediments are described. A valid alternative in term of reliability and costs for the extraction is proposed.